World Health Organization and knowledge translation in maternal, newborn, child and adolescent health and nutrition. Issue 7 (30th December 2021) - ,; Duke, Trevor; AlBuhairan, Fadia S; Agarwal, Koki; Arora, Narendra K; Arulkumaran, Sabaratnam; Bhutta, Zulfiqar A; Binka, Fred; Castro, Arachu; Claeson, Mariam; Dao, Blami; Darmstadt, Gary L; et al.
Abstract : The World Health Organization (WHO) has a mandate to promote maternal and child health and welfare through support to governments in the form of technical assistance, standards, epidemiological and statistical services, promoting teaching and training of healthcare professionals and providing direct aid in emergencies. The Strategic and Technical Advisory Group of Experts (STAGE) for maternal, newborn, child and adolescent health and nutrition (MNCAHN) was established in 2020 to advise the Director-General of WHO on issues relating to MNCAHN. STAGE comprises individuals from multiple low-income and middle-income and high-income countries, has representatives from many professional disciplines and with diverse experience and interests. Progress in MNCAHN requires improvements in quality of services, equity of access and the evolution of services as technical guidance, community needs and epidemiology changes. Knowledge translation of WHO guidance and other guidelines is an important part of this. Countries need effective and responsive structures for adaptation and implementation of evidence-based interventions, strategies to improve guideline uptake, education and training and mechanisms to monitor quality and safety. This paper summarises STAGE's recommendations on how to improve knowledge translation in MNCAHN. They include support for national and regional technical advisory groups and subnational committees that coordinate maternal and child health; support for national plans for MNCAHN and their implementation and monitoring; the production of a small number of consolidated MNCAHN guidelines to promote integrated and holistic care; education and quality improvement strategies to support guidelines uptake; monitoring of gaps in knowledge translation and operational research in MNCAHN. Abstract : Members of the World Health Organization's Strategic and Technical Advisory Group of Experts shares some insights on their approach to knowledge translation to improve child health worldwide.